The health beliefs of patient with type 2 diabetes mellitus who use herbs as a complement to self-care - Anita Joeliantina; Hepta Nur Anugrahini; Jujuk Proboningsih (International Journal of Public Health Science (IJPHS), 2021)
Diabetes mellitus type 2 patients who have a tendency to use herbs, are based on the patient's health belief that herbal medicine is a natural ingredient that has efficacy and is safe. This study aimed to explore health beliefs as predictors of herbal use as a complement to diabetes self-care. A cross-sectional study was conducted on 230 patients with type 2 diabetes mellitus who had been clinically diagnosed, received medical treatment and used herbs. The data was collected using a questionnaire at seven community health centers (Puskesmas) in Surabaya City. Data analysis using Partial Least Square. The indicator of health belief variables has a loading factor value>0.5: perceived vulnerability and severity (0.820), perceived benefits (0.739), perceived barriers (0.822), sense of self-efficacy (0.695). Health beliefs have a significant effect on the use of herbs as a complement to diabetes self-care, the value of T>1.97 (T>10.07). Health beliefs consisting of perceived vulnerability and severity, perceived benefits, perceived inhibition, and perceived self-efficacy were strong predictors associated with the use of herbs as a complement to diabetes self-care. Nurses as part of health workers must pay attention to patient health beliefs in providing education to patients.